2016
DOI: 10.1016/j.vetpar.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of a novel oral formulation of sarolaner (Simparica™) for the treatment and control of fleas on dogs

Abstract: The efficacy of a single oral dose of a novel isoxazoline, sarolaner (Simparica™, Zoetis), for the treatment and control of flea infestations on dogs was confirmed in five laboratory studies. The studies were conducted using adult purpose-bred Beagles and/or mixed breed dogs. All animals were individually identified and housed, and were allocated randomly to treatment with either placebo or sarolaner (eight to 10 per group) based on pretreatment parasite counts. Three studies used cat flea (Ctenocephalides fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Additionally, fleas and ticks can transmit a number of disease organisms that can cause severe, even life-threatening illness in both dogs and humans [24, 25]. Sarolaner belongs to a potent new class of ectoparasiticides (isoxazolines) and when administered as a single-entity (Simparica®, Zoetis) has been shown to provide fast and consistent efficacy against ectoparasites in dogs and cats [2628]. Roundworms and hookworms commonly infect the gastrointestinal tract of dogs and are potentially zoonotic [29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fleas and ticks can transmit a number of disease organisms that can cause severe, even life-threatening illness in both dogs and humans [24, 25]. Sarolaner belongs to a potent new class of ectoparasiticides (isoxazolines) and when administered as a single-entity (Simparica®, Zoetis) has been shown to provide fast and consistent efficacy against ectoparasites in dogs and cats [2628]. Roundworms and hookworms commonly infect the gastrointestinal tract of dogs and are potentially zoonotic [29].…”
Section: Introductionmentioning
confidence: 99%
“…Sarolaner (Simparica®), is a novel oral isoxazoline available in a palatable chewable formulation dosed at monthly intervals. Sarolaner is effective in eliminating existing flea infestations on dogs and provides protective control against reinfestation for 35 days [ 8 , 9 ]. It has been demonstrated that fleas begin to die within 3 to 4 h after sarolaner administration with > 98% elimination of fleas by 8 h and residual efficacy >95.7% within 12 h after reinfestation 35 days post-treatment, which was also sufficient to prevent flea egg deposition during the entire 5-week post-treatment period [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SOK of sarolaner has been compared to that of spinosad (Six, 2016b), afoxolaner (Six et al, 2016c) and fluralaner (Six et al, 2016d). While all four products are known to have rapid SOKs, sarolaner appears to be the most effective on the basis of this work by Six (Six et al, 2016b;2016c;2016d). The most recent of the isoxazolines, lotilaner, has also been shown to have a rapid SOK and to maintain its efficacy between applications (Cavalleri et al, 2017b;2017c).…”
Section: Voltage-dependent Sodium Channel Blockersmentioning
confidence: 88%
“…A single dose of sarolaner resulted in the complete cessation of egg laying for 35 days (Six et al, 2016a). The SOK of sarolaner has been compared to that of spinosad (Six, 2016b), afoxolaner (Six et al, 2016c) and fluralaner (Six et al, 2016d). While all four products are known to have rapid SOKs, sarolaner appears to be the most effective on the basis of this work by Six (Six et al, 2016b;2016c;2016d).…”
Section: Voltage-dependent Sodium Channel Blockersmentioning
confidence: 92%